Ответы и объяснения

2014-03-31T17:30:33+04:00
1.
1). y=(9-7x)^8
y'= 8*(9-7x)^{7}*(9-7x)'=8*(9-7x)^{7}*(-7)=-56*(9-7x)^{7}


2). у= \sqrt{9x+1}
y'= (\sqrt{9x+1})'= \frac{1}{2(9x+1)}·9= \frac{9}{2(9x+1)}

3). y=cos( \frac{x}{2} + \frac{p}{4} )
y'=-sin( \frac{x}{2} + \frac{p}{4} )·( \frac{x}{2} + \frac{p}{4} )'=
-sin( \frac{x}{2} + \frac{p}{4} )·1/2 = -1/2sin( \frac{x}{2} + \frac{p}{4} )

π - заменила p

4). y= \frac{2}{5x+4}
y'= \frac{2'*(5x+4)-2*(5x+4)'}{(5x+4)^{2} } =  \frac{0*(5x+4)-10}{(5x+4)^{2}} =  \frac{-10}{(5x+4)^{2}}

2.
f(x)=x³-3x+7
f'(x)=3x²-3

если f'(x)>0, то
3x²-3>0
x²-1>0
(x-1)(x+1)>0

   +            -              +
------------------------------------------------>
       -1                +1

х∈(-∞;-1)∨(1;+∞)